The Mysterious Universe of the TSH Receptor - Vieira, Inês Henriques; Rodrigues, Dírcea; Paiva, Isabel (Frontiers in Endocrinology, 2022)
The thyroid-stimulating hormone receptor (TSH-R) is predominantly expressed in the basolateral membrane of thyrocytes, where it stimulates almost every aspect of their metabolism. Several extrathyroidal locations of the receptor have been found including: the pituitary, the hypothalamus, and other areas of the central nervous system; the periorbital tissue; the skin; the kidney; the adrenal; the liver; the immune system cells; blood cells and vascular tissues; the adipose tissue; the cardiac and skeletal muscles, and the bone. Although the functionality of the receptor has been demonstrated in most of these tissues, its physiological importance is still a matter of debate. A contribution to several pathological processes is evident in some cases, as is the case of Grave’s disease in its multiple presentations. Conversely, in the context of other thyroid abnormalities, the contribution of the TSH-R and its ligand is still a matter of debate. This article reviews the several different sites of expression of the TSH-R and its potential role in both physiological and pathological processes.